Ethanol Extracts of Achillea millefolium and Hypericum perforatum Low Anti-Toxoplasma Activity - Shagayegh Nozari; Mohtaram Adine; Farzaneh Javadi; Mojtaba Shahnazi; Abbas Azadmehr; Marjan Nassiri-Asl; Hasan Jahanihashemi; Mehrzad Saraei (Journal of Pharmacopuncture, 2016)
Objectives: This study was performed to determine the lethal and the inhibitory effects of ethanol extracts of Achillea millefolium (A. millefolium) and Hypericum perforatum (H. perforatum) on Toxoplasma gondii (T. gondii) RH strain tachyzoites in vitro. Methods: The tachyzoites were treated with concentrations of 10, 50, and 100 mg/mL of A. millefolium and H. perforatum extracts within 10, 30, and 45 minutes in the wells. The mortality rates of tachyzoites treated with extracts were determined by using alkaline methylene blue staining. Also, the tachyzoites in cell cultures were treated with concentrations of 50, 100, and 200 mg/mL of these extracts. The cell viability, inhibition concentration (IC50), and selectivity were determined from MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assays. Results: In the cell-free in vitro study, all of tachyzoites were killed at concentrations of 100 mg/mL of both extracts while at concentration 10 mg/mL, the mortality was 4.53% − 5.31%. In the cell culture study, the values of the effective concentration (EC50) were 215 and 153 μg/mL and the selectivities were 0.73 and 0.69 for the A. millefolium and the H. perforatum extracts, respectively. Conclusion: We conclude that neither extracts has any significant effect on the tachyzoites of T. gondii in cell cultures.